Correlation of Community Knowledge Level and Attitude Towards the Village Self-Service Kiosk Program - Ardiansyah, Muhammad Rici Nur; Nawangsari, Ertien Rining (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The Village Self-Service Kiosk (APMD) is an online service launched by the Tuban Regency Government to simplify the public’s processing of administrative documents. In practice, the program’s success is influenced by several factors, one of which is the community’s level of knowledge about APMD. Insufficient information provision by the implementing agency limits public awareness of the program, which in turn affects attitudes toward its use. According to Ajzen (1991), individuals with greater knowledge tend to hold more positive attitudes and therefore participate more actively, and vice versa. The objective of this research is to identify the relationship between the community's level of knowledge and their attitude towards the APMD program in Jatisari Village. This study employed a quantitative approach using the cross-sectional survey method, involving a predetermined sample of 294 respondents selected through simple random sampling. Data analysis consisted of univariate analysis to determine the frequency distribution for each variable and bivariate analysis, specifically the Spearman Rank correlation coefficient, to identify the relationship between variables. The research findings indicate a